Signal encryption opportunities for photonic networks - Abbade, Marcelo Luís Francisco [UNESP]; Souza, Welerson Santos [UNESP]; Nogueira, Marcelo Pereira [UNESP]; Rodrigues, Ivan Eduardo Lage [UNESP]; de Oliveira Santos, Melissa [UNESP]; Bonani, Luiz Henrique; Aldaya, Ivan [UNESP] (My University, 2020)
We discuss signal encryption opportunities in photonic networks (PNs). In particular, we use computer simulations to show that dynamic keys lead to diffusion when two phase-encoded signals are shuffled and transmitted through PNs.